Rasionalitas Lembaga Keuangan Mikro Syariah di Masa Pandemi Covid-19 - Tenny Badina; Rita Rosiana (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2021)
The purpose of this study is to analyze the rationality of Islamic microfinance institutions in achieving profitability and poverty alleviation missions during the COVID-19 pandemic. The object of this research is the Islamic People's Financing Bank (BPRS) in Banten, DKI Jakarta and West Java Provinces registered with the Financial Services Authority (OJK). The analytical method used is quantitative analysis, with the help of Eviews-9 Software. The results of BOPO, NPF, KAP and PPAP tests on FDR, BOPO, and NPF variables do not affect FDR, so it can be said that the level of BOPO and NPF. In contrast, KAP and PPAP variables have a negative and significant effect on FDR. the results of testing the BOPO, NPF, KAP and PPAP variables on ROA can be concluded that BOPO and NPF variables have a negative effect on ROA. The KAP variable has a positive effect on ROA, while the PPAP variable does not affect ROA.